Análise da comercialização de animais para abate por pecuaristas familiares de diferentes regiões do estado do Rio Grande do Sul - Vargas, Fabiano Vargas de (2019)
The objective of this study was to analyze the representativeness of the commercialization of cattle for slaughter carried out by family farmers from different regions of the state of Rio Grande do Sul, seeking to understand the importance of livestock farming of small businesses and their limitations facing the competitive market of meat under the slaughtering industry. We analyzed the trade relations between the slaughterhouse industry located in the center of the State of Rio Grande do Sul and the family farmers rooted in different meso and micro regions of same State. Collection was performed in the database of the company responsible for the purchase of animals for slaughter, seeking data for the years 2010 to 2013. The characterization between family farmer member or employer was made from the existence of employees or not, declared by rural producers who marketed their lots during the period considered. At the time of sale of animals the rancher who has no rural workers has discount of contribution to the FUNRURAL, based on criteria established by the State Law N°. 13.515 of 13 September 2010. The analysis was performed considering 2.095 sales contracts, carried out by cattle farmer family of differents regions of the state. The methodology used was descriptive statistical analysis, through the Software Microsoft Office Excel, we calculated the numbers of responses, frequency, mean, minimum and maximum values. The analysis made it possible to infer a variation of sales during the months and years surveyed, as well as the participation of women in sales. As regards the amount of business achieved, the analysis showed that there is a greater volume of animals being sold in the first marketing, also noted that it is possible to distribute the epoch of sales in order to fetch better prices . The distribution of family farmers in meso and micro regions in the state was another important data identified by the study, enabling better planning of actions of public officials. Given the above, it is emphasized the importance of studies that facilitate the understanding and recognition of the familiar farmer in the context of the marketing of meat products in the slaughtering industry, organizing actions outside the complex market beef.